Phase transformations in high alloy cold work tool steel - Moravčík, Roman (Strojniški vestnik, 2012)
Phase transformations in the alloy tool steels have a crucial effect on the final properties of the steels. High alloy systems have different solidification conditions compared to construction steels. This paper deals with the phase evolution in high alloy tool steel in quasi-equilibrium state. For analysis various methods such as differential thermal analysis, thermomagnetometry, light microscopy, scanning electron microscopy with energy dispersive analysis, X-ray diffraction analysis and dilatometry, were used. The analysed tool steel solidifies in three steps, and at lower temperatures secondary carbides are formed. Solidification begins at 1340 °C and is finished at 1208 °C. The Curie temperature of this steel is approximately 780 °C.
Keywords: delo v hladnem; diferencialna termična analiza; difrakcijska analiza z X-žarki; dilatometrija; visokolegirano orodno jeklo